LEGAL ANALYSIS OF CORPORATE SOCIAL RESPONSIBILITY OF PUBLIC LIMITED COMPANIES AND STATE OWNED ENTERPRISES - Shandy Chripto Kaunang; Adensi Timomor; Isye Junita Melo (International Journal of Applied Science and Sustainable Development (IJASSD), 2025)
Companies are crucial in fulfilling people's needs for goods and services, but their use of natural resources can harm the environment. Consequently, companies bear a social responsibility to balance economic, social, and environmental interests. Investors must implement corporate social responsibility (CSR) and allocate funds for local welfare, as mandated by Law No. 25 of 2007 on Capital Investment (UUPM). Failure to meet these obligations can result in administrative sanctions, including written warnings, business activity restrictions, suspension of business activities, or revocation of investment facilities. However, the implementation of CSR in Indonesia has its shortcomings due to the absence of ideal regulations, allowing companies to execute CSR based on their own goals. Ideally, CSR should prioritize the local environment before addressing broader environmental concerns. Therefore, this study aims to examine the Legal Arrangements regarding CSR that must be implemented by Public Limited Liability Companies and BUMN in Indonesia, and to explore the obstacles to implementing CSR in Public Limited Companies and BUMN in Indonesia. Using normative legal method, the author found out that Legal regulations regarding Social and Environmental Responsibility (CSR) in Indonesia are contained in various laws, including Law no. 40 of 2007 concerning Limited Liability Companies and PP no. 47 of 2012 concerning CSR of Limited Liability Companies that requires companies, especially those operating in the natural resources sector, to implement CSR. Some companies only carry out CSR as a formality without any significant impact on society and the environment. The absence of comprehensive standard guidelines causes confusion and inefficiency.